An Analysis of Figurative Languages in the Niki Zefanya’s Song Lyrics - Zahria, Salma Talita; Wibowo, Hanafi (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2024)
Language and music are deeply interconnected, enabling artists to express emotions and abstract ideas creatively. While figurative language is a key element in literary and musical compositions, limited research has examined how emerging contemporary musicians employ it to enhance lyrical expression. This study investigates the use of figurative language in three selected songs by Niki Zefanya. Using a qualitative approach with textual analysis, this research identifies and categorizes figurative devices present in the lyrics. The findings reveal five types of figurative language: metaphors and hyperboles as the most dominant, followed by irony, synecdoche, and repetition, each contributing to the emotional and thematic depth of the songs. These results highlight the role of figurative language in shaping meaning, enhancing artistic expression, and deepening listeners’ engagement with song lyrics. This study contributes to the fields of stylistics and discourse analysis by offering insights into the intersection of language and music, demonstrating how figurative language functions as a communicative tool in contemporary songwriting.